Pengaruh Kompensasi, Lingkungan Kerja Terhadap Produktivitas Karyawan : Studi Kasus pada Bumdes Desa Kedungudi Kecamatan Trawas Kabupaten Mojokerto pada Bidang Pariwisata - Mukhammad Rafie Afgiansyah; Hartono Hartono; Agoes Hadi Poernomo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Compensation and the work environment are two essential factors that significantly affect employee productivity, particularly in community-owned enterprises (BUMDes) engaged in the tourism sector. A fair remuneration system motivates employees to work optimally, while a supportive physical and psychosocial work environment creates comfort that enhances job performance. This study aims to examine the influence of compensation and work environment on employee productivity in BUMDes Kedungudi, which serves as one of the local driving forces in developing tourism-based community economic empowerment. This research employed a quantitative approach using a survey method with a total sample of 37 tourism sector employees of BUMDes Kedungudi. Data were collected through structured questionnaires, which were subsequently analyzed using SPSS version 28. The analytical procedures included validity and reliability testing, classical assumption testing such as normality, multicollinearity, and heteroscedasticity checks, as well as multiple linear regression analysis to determine the effect of independent variables on employee productivity. The results revealed that both compensation and work environment had a positive and significant influence on productivity. Specifically, compensation demonstrated a coefficient value of β = 0.205 with a significance level of p = 0.007, while the work environment showed a stronger effect with β = 0.281 and p = 0.002. Furthermore, the regression model indicated that the combination of these two variables was able to explain 68.0% of the variance in employee productivity (Adjusted R² = 0.680; p < 0.001). This finding highlights the strategic importance of remuneration policies and workplace conditions in enhancing organizational performance within community-owned enterprises.